The Effect of Product Quality and Promotion on Purchasing Decisions: Study on Consumers of A Beauty Company in Bandung - Fatya Anissa Arliandhini; Retno Resawati (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
The present study emerged from the recognized concern surrounding consumers' decision-making process when purchasing a product from a beauty company located in Bandung. The primary issue identified in this study pertains to the diminished purchasing decisions resulting from the inadequate quality of the product and promotional efforts. This research aims to investigate the impact of product quality and promotion on consumer purchasing behavior for a beauty product offered by a company in the city of Bandung. The present study utilizes descriptive and confirmatory methodologies, employing a quantitative research approach. The research sample comprises consumers of a product offered by a beauty company located in Bandung, with 100 participants residing in the city of Bandung. The findings indicate a strong and statistically significant relationship between product quality and consumer purchasing behavior. Likewise, the influence of promotional activities on consumer purchasing decisions is positive and statistically significant. The correlation coefficient demonstrates a robust relationship.